Organic reaction mechanisms, 2009 : an annual survey covering the literature dated January to December 2009 - Knipe, A. C. (Chichester, U.K. : Wiley, 2012)
Organic Reaction Mechanisms 2009, the 45th annual volume in this highly successful and unique series, surveys research on organic reaction mechanisms described in the available literature dated 2009. The following classes of organic reaction mechanisms are comprehensively reviewed: & bull; Reaction of Aldehydes and Ketones and their Derivatives & bull; Reactions of Carboxylic, Phosphoric, and Sulfonic Acids and their Derivatives & bull; Oxidation and Reduction & bull; Carbenes and Nitrenes & bull; Nucleophilic Aromatic Substitution & bull; Electrophilic Aroma.
Front Matter -- Reactions of Aldehydes and Ketones and their Derivatives / B A Murray -- Reactions of Carboxylic, Phosphoric, and Sulfonic Acids and their Derivatives / C T Bedford -- Oxidation and Reduction / R N Mehrotra -- Carbenes and Nitrenes / E Gras -- Nucleophilic Aromatic Substitution / M R Crampton -- Electrophilic Aromatic Substitution / R G Coombes -- Carbocations / R A McClelland -- Nucleophilic Aliphatic Substitution / K C Westaway -- Carbanions and Electrophilic Aliphatic Substitution / M L Birsa -- Elimination Reactions / M L Birsa -- Addition Reactions: Polar Addition / P Kocovsky -- Addition Reactions: Cycloaddition / N Dennis -- Molecular Rearrangements: Part 1. Pericyclic Molecular Rearrangements / S K Armstrong -- Molecular Rearrangements: Part 2 / J M Coxon -- Author Index -- Cumulative Subject Index, 2005-2009.
Includes bibliographical references and indexes.
Print version record.
Keywords: Organic reaction mechanisms; SCIENCE -- Chemistry -- Organic; Organic reaction mechanisms; Electronic books; Electronic books